Pengaruh Penghindaran Pajak, Kinerja Keuangan dan Leverage Terhadap Nilai Perusahaan - Sianne Wella; Emmiliana Hartanti (UNIVERSITAS KALBIS, 2022)
This research was aimed to know the influence of tax avoidance, financial performance and leverage on firm value. In this study, the sampel used are the listed companies of Indonesia Stock Exchange (BEI) in 2016-2018 with 58 sample companies by using a purposive sampling technique. This research used panel data regression method with random effect approach model. The results show that tax avoidance and leverage has no influence on firm value, whereas, financial performance has influence on firm value.